Computed Tomography (CT) and Pathologic Correlation of Ovarian Tumours in children & adolescents: A review of eight cases - Hassan, Radhiana; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Abdullah, Suhaiza (2011)
Ovarian tumours are an uncommon form of childhood neoplasm. About 75% of ovarian tumours in children less than 18 years of age were benign, 20% malignant and 5% potentially malignant. There was little difference in the clinical presentation of children with benign versus malignant tumours. Abdominal radiograph (AXR), ultrasonography (US) and computed tomography (CT) are imaging modalities, which are widely used in the assessment of ovarian mass in these patients.